Pengembangan Sistem Informasi Penjualan Motor berbasis Web menggunakan Teknologi Firebase (Studi Kasus: Dealer Motor "Suzuki Katang") - Teresa Narwastu; Buce Trias Hanggara; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
â€œSuzuki Katangâ€ Motorcycle Dealer is one of the Suzuki brand motorcycle distributors located in Kediri City which was founded in 2010. In its business process, namely bookkeeping, before using Microsoft Excel, dealers used the manual method using a notebook. In addition, they have also used the google form but it is not effective because they have to access a different google form for other types of data. If the service process does not run smoothly it will leave a bad score for the buyer. In addition, every month an evaluation is usually held by an official dealer. Which, if the evaluation of service evaluation and presentation of sales reports is not satisfactory, it will affect the capacity of the unit that can be ordered by the dealer as well as the limited cooperation carried out with other authorized dealers. From these issues, it is important to foster a business data framework for better information the executives. The motivation behind this exploration is to foster a business data framework in the form of a web using Javascript and utilize the Firebase Realtime Database service. System requirements analysis session totals 12 requirements functionality and 1 non-functionality. In testing, using validation testing to users for the overall system function testing results are 100% valid. Non-functionality testing uses the Framework Usability Scale (SUS) technique which is acquired from polls that have been replied by respondents from Suzuki Katang business representatives. From the consequences of the tests did, it was tracked down that the classification was acceptable and the adjective rating was OK with a value of 74, 2.